2005
DOI: 10.3168/jds.s0022-0302(05)72808-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yeast Culture and Galacto-Oligosaccharides on Ruminal Fermentation in Holstein Cows

Abstract: Four nonlactating, ruminally cannulated Holstein cows were used in a 4 x 4 Latin square design, balanced for residual effects, to evaluate the effects of supplementing dairy cow diets with yeast culture (Trichosporon sericeum; YC), galacto-oligosaccharides (GOS), or the mixture of YC and GOS on ruminal fermentation, microbial N supply, in situ degradation, and energy and nitrogen metabolism. Treatments were arranged in a 2 x 2 factorial as follows: 1) basal diet, 2) basal diet plus 10 g/d YC, 3) basal diet plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
18
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
5
18
1
1
Order By: Relevance
“…In the present study, the rumen ammonia concentration was not affected by the yeast addition, as reported by others (Lila et al, 2004;Mwenya et al, 2005), although slight decreases in the ammonia concentration by LYC and YC for the L-NDF diet were observed. Decreased ammonia concentrations in the rumen caused by Saccharomyces cerevisiae were reported by Abd-El-Ghani (2004) and may indicate lower protein decomposition as well as faster flow of undegraded protein to the duodenum.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, the rumen ammonia concentration was not affected by the yeast addition, as reported by others (Lila et al, 2004;Mwenya et al, 2005), although slight decreases in the ammonia concentration by LYC and YC for the L-NDF diet were observed. Decreased ammonia concentrations in the rumen caused by Saccharomyces cerevisiae were reported by Abd-El-Ghani (2004) and may indicate lower protein decomposition as well as faster flow of undegraded protein to the duodenum.…”
Section: Resultssupporting
confidence: 88%
“…Piva et al (1993) observed a reduction of the acetate:propionate ratio when YC was fed to lactating cows, while total VFA was not affected. Mwenya et al (2005) reported increasing VFA concentrations, especially those of acetate and isoacids, in the rumen fluid and this may have indicated increased activity of cellulolytic bacteria. This effect was not observed in the present study.…”
Section: Resultsmentioning
confidence: 92%
“…Yeasts, in particular different strains or commercial products of Saccharomyces cerevisiae, have been tested on dairy cows with a number of positive effects such as increased dry matter intake (DMI) and milk production (Wohlt et al,1998;Dann et al, 2000); improved diet digestibility (Erasmus et al, 1992;Marden et al, 2008); stabilized rumen pH (Bach et al, 2007); and stimulated rumen bacteria growth (Newbold et al, 1995). However, there are also many studies with no or negative responses to yeast supplementation (Mwenya et al, 2005;Longuski et al, 2009;Chung et al, 2011), probably related to the strong influence of the basal diet, the variation in yeast strains and the different commercial formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Although some prebiotics such as scFOS, OF, inulin, mannanoligosaccharides (MOS) and galactooligosaccharides have been supplemented to cows (Mwenya et al, 2005), calves (Masanetz et al, 2011) and lambs (Thayne, 2007) and some information is available on the effects of feeding prebiotics in selected species mentioned above (Swanson et al, 2002a), there is no information on the effects of supplemental inulin in kids.…”
Section: Introductionmentioning
confidence: 99%